Hospice Counsellor Facing the Grief of the Terminally Ill Child and Its Family - Grzegorz Godawa (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2012)
The child’s illness, suffering and death provoke many emotions in the family. The ill child and its family both experience grief which is an emotional reaction to the danger of losing health or life. Support offered by home hospices for children aims at overcoming the destructive influence of illness. A hospice counsellor’s task is to improve the ill child and its family’s quality of life. He is helping the family overcome grief and prepare for the child’s death. The hospice team supports the family members who experience anticipatory and later, actual mourning. Preventing pathological effects of grief is a basic challenge for people who offer help.